METHODICAL RECOMMENDATIONS ABOUT ORGANIZATION OF MAMMALS HELMINTH FAUNA STUDY IN PROTECTED AREAS - E. A. Vlasov (Российский паразитологический журнал, 2016)
In this article is shortly described methods of study of helminth fauna of mammals in protected areas. Methods and results that kind of study are depicted by the example of researches which were carried out in the Central-Chernozem state nature reserve inKurskoblast. These methodical recommendations intended for researchers of reserves, national parks, parasitologists, mammalogists and broad zoologists.